Investigation of the bioactivity and antibacterial activity of porous hydroxyapatite ceramics derived from natural sources - Jatsada Wadthanakul; Phanrawee Sriprapha; Narongdech Boothrawong; Komsanti Chokethawai; Chamnan Randorn; Waraporn Boontakam; Nopakarn Chandet; Kriangkrai Thongkorn; Gobwute Rujijanagul (Journal of Asian Ceramic Societies)
Normally, hydroxyapatite (HAp) ceramics have no antimicrobial activity. Therefore, the development of the HAp with enhanced antimicrobial characteristics is essential for the prevention of infections associated with medical implants. In this research article, porous hydroxyapatite (HAp) ceramics were synthesized via a simple thermal decomposition of bovine bone. All synthesized samples contained the main phase of HAp. However, beta tricalcium phosphate (β-TCP) started to form at 900°C, and its amount increased with increasing firing temperatures. Crystallite size increased with firing temperatures then dropped at temperatures > 1200°C. The decrease of this value was related to the β-TCP formation. Microstructural analysis revealed that the 900°C sample had a good uniform porous structure with an average pore size of 0.39 μm. The 900°C samples were coated with antimicrobial agents, including Ag-based agents (Ag nanoparticles and AgNO3) and natural plant oils (lemongrass and turmeric oils), to improve their antimicrobial activity. The samples coated with Ag-based agents presented good antimicrobial efficiency while natural plant oil-coated samples showed moderate efficiency. The obtained results suggested the possibility of developing porous samples for antimicrobial applications, using natural sources at a low cost.